Growth and yield of direct seeded rice as influenced by irrigation levels and varieties (Bangladesh Journal of Botany, 2024)
The combined influence of agronomic, environmental and genetic variables results in better crop yield. Among these components, an appropriate irrigation system and varietal choice are crucial. With this background, a field experiment with a split-plot layout was planned during the summer period of 2020 at the Agriculture and Horticultural Research Station, Bhavikere, Karnataka, India, to examine the effects of four different irrigation levels (0.75, 1.00, 1.25 and 1.50 IW/CPE ratio) in the main plot and four different varieties (Local variety, Jyothi, MAS 946-1 and MAS-26) in the subplots on growth and yield performance under direct seeded rice condition. Results of the experiment revealed that among four different levels of irrigation, scheduling irrigation at 1.50 IW/CPE ratio recorded higher growth and yield parameters at harvest viz., plant height (82.76 cm), number of tillers per plant (13.29), leaf area index (2.66), total dry matter accumulation (73.36 g/plant), number of panicle per plant (10.35), panicle length (21.59 cm), number of filled grains per panicle (90.4), grain yield (5569 kg/ha) and straw yield (7514 kg/ha). While, among the varieties used for the study, MAS 946-1 recorded the higher growth and yield parameters at harvest (64.19 cm, 13.96, 2.45, 73.34 g/plant, 10.96, 21.25 cm, 84.3, 5743 kg/ha and 7288 kg/ha, respectively). Hence, scheduling irrigation at 1.50 IW/CPE ratio and use of MAS 946-1 variety demonstrated superior performance, making it most appropriate for maximising higher production under direct seeded rice condition.Bangladesh J. Bot. 53(3): 527-533, 2024 (September)